PARAPROSTATIC CYST IN A DOG - Canpolat, I.; Eroksuz, Y. (Indian Veterinary Journal, 2008)
Prostatic cysts in the dog include diffuse cystic change associated with androgen - dependent BPH, as well as retention or paraprostatic cysts, which are cavitating lesions with a distinct wall, containing clear to turbid fluid, either within (retention) or outside (paraprostatic) the prostatic parenchyma (White et al., 1987). Pathogenesis is unknown, paraprostatic cysts usually arise craniolateral to the prostate, displacing the bladder cranially and ventrally, or caudal to the gland within the pelvis, as possible dilated embryonal remnants of Wolffian ducts. Mean age at the time of diagnosis is reported as 8.0 years (Olson et al., 1987, Krawiec and Heflin 1992). A case of paraprostatic cyt3 in a dog is reported.
Keywords: Prostatic Disease; Diagnosis